Developing a Renewable Energy-Based Tourism Areas and Empowerment Micro and Small Enterprises: Pengembangan Kawasan Wisata Berbasis Energi Terbarukan dan Pemberdayaan UMKM - Nila Alia; Hapsari, Ratih Indri; Perdana, Fengky Adie; Nugroho, Pipit Wahyu; Udianto, Pondi; Widjanarko, Widjanarko (Universitas Lancang Kuning, 2025)
Wringinsongo Village is a foster village by State Polytechnic of Malang that has the potential for nature-based tourism, particularly in the Sumberingin bathing site, which is enriched with water resources. Although the tourism infrastructure, such as cafes, stalls, and transportation access, is sufficient, the operational hours are limited to only 4 PM due to the lack of adequate lighting systems. The objective of this community service is to provide a 2200 Wp Solar Power Plant (PLTS) and an energy storage system using batteries, as well as to facilitate the legal assistance for MSME entrepreneurs in the Sumberingin bathing area. The methodology applied follows an asset-based community development approach, emphasizing technology transfer through fulfilling the need for off-grid solar power systems for lighting and electricity. It also includes the development of educational facilities for solar energy, training on the maintenance and repair of the PLTS, and assistance in the legal formalization of businesses for MSME entrepreneurs. The results of the community service activities offer a solution for independent energy fulfillment through the implementation of environmentally friendly solar power systems, enhancing knowledge and adding value to the tourist site as an educational tourism destination based on renewable energy. Furthermore, the activities also contribute to MSMEs in the Sumberingin tourism area by facilitating their business legality. Following the completion of the community service program, all MSMEs have obtained Business Identification Numbers (NIB), laying the foundation for more formal business development and integration into a broader economic system